2019
DOI: 10.1002/jmri.26692
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility‐weighted imaging in malignant melanoma brain metastasis

Abstract: Background The value of cerebral susceptibility‐weighted imaging (SWI) in malignant melanoma (MM) patients remains controversial and the effect of melanin on SWI is not well understood. Purpose To systematically analyze the spectrum of intracerebral findings in MM brain metastases (BM) on SWI and to determine the diagnostic value of SWI. Study Type Retrospective. Population/Subjects In all, 100 patients with melanoma BM (69 having received radiotherapy [RT] and 31 RT‐naïve) and a control group of 100 melanoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In the case of brain metastases from systemic melanoma or breast cancer, T1-Gd has been shown to be better than other modalities (15,20). Moreover, in direct comparison with T1-Gd for detecting melanoma metastases, SWI-U has shown no diagnostic advantage (21). To our knowledge, the present study is the first one to prospectively evaluate the added value of SWI-Gd for the potential detection of brain metastases.…”
Section: Discussionmentioning
confidence: 79%
“…In the case of brain metastases from systemic melanoma or breast cancer, T1-Gd has been shown to be better than other modalities (15,20). Moreover, in direct comparison with T1-Gd for detecting melanoma metastases, SWI-U has shown no diagnostic advantage (21). To our knowledge, the present study is the first one to prospectively evaluate the added value of SWI-Gd for the potential detection of brain metastases.…”
Section: Discussionmentioning
confidence: 79%
“…This was first reported by Gaviani et al on T2 * -weighted imaging in three malignant melanoma patients (52). However, later studies analyzing the fate of isolated cerebral SWI artifacts in larger patient cohorts over time could not confirm the hypothesis that such "isolated SWI signals" would eventually evolve into overt brain metastases (53,54). Indeed, these studies showed that SWI signal losses without corresponding signal changes on standard sequences remained constant over time.…”
Section: Swi In Melanoma Brain Metastasesmentioning
confidence: 89%
“…The SWI signal drop remains as a remnant of the preexisting metastasis (iv). Adapted from Schwarz et al (54).…”
Section: Swi In the Assessment Of Treatment Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…37 These changes could be evaluated on SWI following SRS which allow for the assessment of treatment response along with T1 post-contrast images. 38,39 The purpose of our study was to extend previous work and evaluate the longitudinal change of intratumoral susceptibility signal (ITSS) on highresolution SWI as an adjunctive imaging tool to evaluate treatment response of brain metastasis following stereotactic radiosurgery. Our hypothesis is that this approach could help further stratification of the patients and guide clinical decision making.…”
Section: Introductionmentioning
confidence: 99%